Customer perception towards tesla electric car’s innovative features - DR. GIGI G S,; MR. RAJKARAN L.S, (The journal of contemporary issues in business and government, 2020)
This paper is titled as the customer perception towards Tesla electric cars innovative features. The objective of this particular research was to study the minds and thoughts that the customers had towards electric cars. Electric cars are the future living cars that will be established soon for the customers experiences. The study involves descriptive methodology with the help of primary and secondary data and the survey was taken from 76 respondents, the target audience, the customers for the analyzing purposes. Further the finishing were calculated with the help of statistical tools.